Study of Pappasang in The Text of Marriage Advice in Mappakasunggu District takalar regency - Hani Wulandari Hamsah; Kembong Daeng; Asia M (Universitas Negeri Makassar, 2021)
This study aims to describe the meaning of pappasang, and cultural values contained in the text of marriage advice in District Mappakasunggu Takalar Regency. Based on the semiotics theory of Charles Sanders Peirce.This research uses a qualitative descriptive approach, data analysis techniques obtained through documentation methods. There are two main issues examined in the text of marriage advice, namely: first the meaning contained in the text of marriage advice, and the second is what values are contained in the text of marriage advice. The results of this study showed that in terms of the meaning of pappas in the text of marriage advice can be obtained. In terms of the meaning of pappasang is the message of parents first containing instructions, advice, and mandates that must be carried out in order to live a good life. And from that explanation contains icons, indexes, and symbols of instructions on what to do, what to do, what to do, and what not to do. And in terms of the values contained in the text of marriage advice can be obtained values namely, the value of honesty, the value of sirik na pacce, the value of unity and mutual cooperation, the value of effort and hard work.